In vitro effect of lemon essential oil and garlic extract on Monilinia fructicola growth - Mitidieri, Mariel Silvina; Barbieri, Martin Osvaldo; Brambilla, Maria Virginia; Piris, Estela Beatriz (INIA Uruguay y Facultad de Agronomía, Universidad de la República, 2021)
Brown rot produced by Monilinia fructicola (MON) is the main disease that causes postharvest losses in peaches of Argentina. There is a public concern in reducing the use of synthetic fungicides. The objective of this work was to evaluate the effect of lemon essential oil (LO) and aqueous garlic extract (GE) on MONin vitro mycelial growth inhibition (INH). In a first trial a MON colony disc was placed in the middle of a Petri dish containing PDA2%, or over the plate lid containing 1 mL of the following treatments: Control, LO 0.5%, LO 1%, LO 3% and Fludioxonil 0.02%. In a second trial, GE was obtained processing fresh garlic (cultivar Colorado) in a blender with tap water; 1 mL of garlic extract was placed in the cover of each plate, the treatments were: Control, GE 2.27%, GE 5.68%, GE 11.35% and Fludioxonil 0.02%, the MON colony was placed over the lid containing the extract. All concentrations of LO assayed and GE 11.35% showed INH > 90%. Following these results LO and GE could be evaluated in future trials as postharvest treatments on peach fruits for Monilinia fructicola control.